The Use of Augmented Reality through Assemblr Edu to Inspire Writing in an Ecuadorian EFL Distance Program - Carrión-Robles, Fernando; Espinoza-Celi, Verónica; Vargas-Saritama , Alba (International Journal of Engineering Pedagogy (iJEP), 2023)
This study analyzed the effectiveness of using augmented reality (AR) through the Assemblr Edu platform to improve English as a foreign language (EFL) writing skills in distance education. The participants included 40 freshmen university students who speak English at a basic level. This case study was approached through the mixed method. The data collection instruments encompassed a pre-test, a post-test, written tasks assessed through a rubric, and a survey. Findings evidenced that Assemblr Edu enhanced participants’ writing-skill development in terms of organization and structure of paragraphs as well as grammar, vocabulary, and punctuation. This was thanks to the augmented reality elements in 3D, which allowed the designing of teaching material incorporating interactive activities, videos, images, and multimedia elements.